E-ASSESSMENT DESIGN DEVELOPMENT IN ENTREPRENEURIAL LEARNING - Umi Nuraini; Primasa Minerva Nagari; Nur Alfiyatuz Zahro; Nuventin Asna Putri (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Assessment is a fundamental aspect of learning and becomes a challenge in online learning in the area of disruption. Besides being able to improve the professional competence of educators, the proper application of e-assessment can help students to have the competencies needed in the 21st century. This study aims to develop an e-assessment design in entrepreneurial learning in Accounting Department Universitas Negeri Malang, Indonesia. This e-assessment, which is designed to assess students’ knowledge, attitudes, and skills, becomes more efficient and transparent and is easily accessible to students. The results of this study are not only useful for lecturers in the process of designing e-assessments but also for undergraduate students of Accounting Education as prospective accounting educators so that they know in real-life contexts that can be learned and applied in educational courses. The development of the e-assessment design in this study can be used as a reference for other researchers in developing e-assessments in other subjects, but still must adapt it to the curriculum and learning system that applies at the university.